Synergistic Induction of t-PA by Vascular Endothelial Growth Factor and Basic Fibroblast Growth Factor and Localization of t-PA to Weibel-Palade Bodies in Bovine Microvascular Endothelial Cells - Pepper, Michael S.; Rosnoblet, Corinne; Sanza, Corinne Di; Kruithof, Egbert K. O. (Thrombosis and Haemostasis, 2001)
Endothelial cell migration is stimulated by members of the vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF) families, and is dependent on extracellular proteolytic activity provided by enzymes of the plasminogen activator (PA) system. Here we report that in bovine microvascular endothelial cells (BME cells), bFGF principally increased urokinase-type PA (u-PA) while tissue-type PA (t-PA) was increased mainly by VEGF. In bovine aortic endothelial cells (BAE cells), bFGF increased u-PA, whereas VEGF had no effect. Co-added bFGF and VEGF increased t-PA mRNA levels and enzyme activity in both cell types in a synergistic manner. Tissue-type plasminogen activator (t-PA) immunoreactivity colocalized with von Willebrand factor, a marker for Weibel-Palade bodies. Co-added bFGF and VEGF increased the number of t-PA-positive cells as well as the number of t-PA-positive granules per cell. Localization of t-PA in regulated storage granules endows endothelial cells with the potential to rapidly increase proteolytic activity in the pericellular environment.
Keywords: Angiogenesis; cytokine; protease; matrix